Problems of teaching vocabulary for the formation of writing skills for foreign students, studying the Kazakh and Russian languages (Eurasian Journal of Philology Science and Education, 2019)
This article discusses the problems of learning vocabulary for the formation of writing skills in foreignstudents learning Kazakh and Russian languages. This article provides various guidelines, corresponding to different stages of training. For the formation of various writing skills offered interactive forms.The system of exercises presented in this article contributes to the development of writing communication. Teaching – a complex and multipronged process. The activities of the teacher should be aimedto maximize the learning process. Accounting for these moments allows the teacher to build a classmethodically competently, to adjust their pace, alternate forms of work, that means to intensify the activities of the students. Communicative principle, which became the base for most of didactic conceptsand successfully implemented in almost all stages of education, largely strengthened ties methodologyand linguistics, increased interest in teaching communicative process parameters. In the article, variousmethodic recommendations are provided, which correspond to various stages of education. It is givenattention not only to linguistic form of expression, but to informal form. Interactive forms of teachingare proposed for speaking. System of exercises, provided in the article, contributes to development ofwriting communicative.